2015
DOI: 10.1089/mab.2014.0075
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Marker for Undifferentiated Human Embryonic Stem Cells

Abstract: Human embryonic stem cells (hESCs) are pluripotent stem cells from early embryos, and their self-renewal capacity depends on the sustained expression of hESC-specific molecules and the suppressed expression of differentiation-associated genes. To discover novel molecules expressed on hESCs, we generated a panel of monoclonal antibodies against undifferentiated hESCs. The antigen recognized by MAb2 is expressed on the cell surface of undifferentiated hESCs; three diffused bands with molecular mass between 30 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…21 CD147/EMMPRIN is an important marker for anchorage independent growth, angiogenesis, drug resistance, hypoxic survival, and invasion, properties attributed to CSCs and which are essential molecular events for carcinogenesis. 22 Additionally, CD147 is also a marker of undifferentiated human embryonic stem cells 23 and has been reported as a marker of oral CSCs. 24 Recent studies have implicated CD147, along with CD44, in modulation of the Wnt/β-catenin pathway 25 in metastatic prostate cancer, a property which is being investigated as potential therapeutic strategy.…”
Section: Discussionmentioning
confidence: 99%
“…21 CD147/EMMPRIN is an important marker for anchorage independent growth, angiogenesis, drug resistance, hypoxic survival, and invasion, properties attributed to CSCs and which are essential molecular events for carcinogenesis. 22 Additionally, CD147 is also a marker of undifferentiated human embryonic stem cells 23 and has been reported as a marker of oral CSCs. 24 Recent studies have implicated CD147, along with CD44, in modulation of the Wnt/β-catenin pathway 25 in metastatic prostate cancer, a property which is being investigated as potential therapeutic strategy.…”
Section: Discussionmentioning
confidence: 99%
“…As an adhesion molecule, CD147 is widely expressed in a variety of cancer types. Recently, Higashi et al (29) demonstrated that CD147 may be an undifferentiated marker of human embryonic stem cells. Despite substantial progress of CD147 in cancer pathogenesis, the biological roles of CD147 are not clear in CSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Cultures of Oct-4 lung stem cells could be infected with SARS-CoV with subsequent virus replication, suggesting that failing lung repair of SARS-CoVinfected involves the loss of mobilization and differentiation of lung stem and progenitor cells. On the other hand, CD147, the second entry receptor for SARS-CoV-2, has been proposed to be a marker protein of undifferentiated embryonic stem cells, and the monoclonal antibody against this protein also stained lung cancer cells [29]. It is possible that CD147 is also expressed by untransformed lung stem and progenitor cells; however, to the best of our knowledge, there is no experimental evidence for such affirmation.…”
Section: Stem Cell Facets In Covid-19: Possible Target For Infectionmentioning
confidence: 95%